Los Caballeros Jerezanos en la “Nómina de la Frontera” de 1290 - Sánchez Saus, Rafael (En la España Medieval, 2006)
A study of the fifty-one knights from Jerez de la Frontera mentioned in 1290 as royal vassals in the document termed “Nómina de la Frontera”, deposited in the Cathedral Archive of Toledo. Research reveals extensive personal and familial connections between knights from Jerez and Seville, establishes remarkable continuity between the settlers established in Jerez in 1265 and the knights of 1290, reinforces the role of certain extensive family groups in the tasks of defending and resettling Andalusia and resolves that nobles had an importance heretofore ignored in the early days of Christian and Castilian Andalusia.